Efficacy of 1 g Ceftriaxone Monotherapy Compared to Dual Therapy With Azithromycin or Doxycycline for Treating Extragenital Gonorrhea Among Men Who Have Sex With Men. (17th May 2021) - Aoki, Takahiro; Mizushima, Daisuke; Takano, Misao; Ando, Naokatsu; Uemura, Haruka; Yanagawa, Yasuaki; Watanabe, Koji; Gatanaga, Hiroyuki; Kikuchi, Yoshimi; Oka, Shinichi
Abstract: Background: Evidence on efficacy of high-dose ceftriaxone monotherapy for extragenital Neisseria gonorrhoeae (NG) infection is lacking. Methods: A cohort of men who have sex with men (MSM) were tested for NG/ Chlamydia trachomatis (CT) every 3 months, in a single-center observational study in Tokyo, Japan. MSM aged > 19 years diagnosed with extragenital NG infection between 2017 and 2020 were included. A single dose of 1 g ceftriaxone monotherapy was provided, while dual therapy with a single oral dose of 1 g azithromycin or 100 mg doxycycline administered orally twice daily for 7 days were given, for those coinfected with CT, according to infected sites. Efficacy of these treatments was calculated by the number of NG-negative subjects at test-of-cure divided by the number of subjects treated. Fisher exact tests were used to compare the efficacy between the 2 groups. Results: Of 320 cases diagnosed with extragenital NG, 208 were treated with monotherapy and 112 were treated with dual therapy. The efficacy against total, pharyngeal, and rectal infections was 98.1% (204/208, 95% confidence interval [CI]: 95.2–99.3%), 97.8% (135/138, 95% CI: 93.8–99.4%), and 98.6% (69/70, 95% CI: 92.3–99.9%), respectively, in the monotherapy group, whereas the corresponding efficacy in the dual therapy was 95.5% (107/112, 95% CI: 90.0–98.1%), 96.1% (49/51, 95% CI: 86.8–99.3%), and 95.1% (58/61, 95% CI: 86.5–98.7%), respectively. No significant difference in the corresponding efficacy was observed between the two groups ( P = .29, P = .61, P = .34, respectively). Conclusions: High-dose ceftriaxone monotherapy is as effective as dual therapy for extragenital NG among MSM. Abstract : Ceftriaxone monotherapy is as effective as dual therapy with azithromycin or doxycycline for treating pharyngeal and rectal infections of Neisseria gonorrhea in men who have sex with men. Thus, monotherapy may be preferred when there are no coinfections.